Optical Measurement of Cable and String Vibration - Y. Achkire; A. Preumont (Shock and Vibration)
This paper describes a non contacting measurement technique for the transverse vibration of small cables and strings using an analog position sensing detector. On the one hand, the sensor is used to monitor the cable vibrations of a small scale mock-up of a cable structure in order to validate the nonlinear cable dynamics model. On the other hand, the optical sensor is used to evaluate the performance of an active tendon control algorithm with guaranteed stability properties. It is demonstrated experimentally, that a force feedback control law based on a collocated force sensor measuring the tension in the cable is feasible and provides active damping in the cable.